On/Off Temperature Monitoring and Control via the Internet of Things Using iTCLab Kit - Basuki Rahmat; Minto Waluyo; Tuhu Agung Rachmanto (Future Science, 2022)
With the Internet of Things (IoT) gradually evolving as the next phase of the Internet's evolution, it becomes important to recognize the various potential domains for IoT deployments, and research challenges especially those related to monitoring and control applications in industry. This paper shows how to program a simple On/Off temperature control system via IoT using Arduino and the iTCLab Kit. Meanwhile, for monitoring and controlling temperature via cellphone, the IoT MQTT Panel is used. The experimental results show that the control system has worked well. This is indicated by controlling and monitoring the results of temperature control via cell phone as expected.